MAKNA STRATEGIS PENGAJARAN BAHASA INGGRIS DI SD - Agus Widyantoro, Agus Widyantoro (Jurnal Cakrawala Pendidikan, 2016)
The teaching of English in elementary schools has a strategic and anticipatory significance. The results of the teaching of English at present will affect the quality of the Indonesian human resources early in the coming 21 * century. Because at that time Indonesia will enter the free market era, improvements on the quality of the human resources through the teaching of English have to receive enough attention from all parties involved. In addition, the teaching of English in elementary schools will become the basis for that at higher levels. Failure in the teaching of English in elementary schools will exert negative effects on the success of such teaching at higher levels.